SURVIVAL AND BETTERMENT: THE ASPIRATIONS OF FOUR MEDIEVAL GENTRY FAMILIES AS REVEALED IN THEIR LETTERS. (1st October 2012) - Kirby, Joan W
Abstract : Covering the period 1290-1584, the Paston, Plumpton, Cely and Stonor letters, although for the most part 'business letters', concerned with the administration of their households and estates, nevertheless throw fascinating light on aspects of contemporary society. They reveal that the lives of those who strove to survive and prosper as landowning gentry were played out against a background of civil war, violent Scottish incursions over the northern borders, and military reversals in France. Closer to home, they struggled with predatory lords, tight-fisted dowagers, disgruntled sons, wretched daughters and bitterly contested wills. Faced with many imponderables, they marshalled their defences: judicious marriages and kinship networks, compliant children, the patronage of influential magnates - perhaps even of the king himself, such protection as was afforded by the law and unceasing vigilance. Parental affection and true love and devotion also find welcome expression among what were severely practical concerns.